2005
DOI: 10.20467/1091-5710.9.3.51
|View full text |Cite
|
Sign up to set email alerts
|

Caring in Action: The Patient Care Facilitator Role

Abstract: The downsizing movement left fractures in the healthcare system for patients, nurses, and healthcare providers. To heal the fractures, nurses at the Baptist Hospital of Miami developed the patient care facilitator (PCF), a clinical leadership role for nurses within a smaller area of patient responsibility (12-bed hospital), to provide caring professional nursing practice for both patients and staff. This article describes the multimethod research done to evaluate the impact of the role on continuity of care fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…One interesting finding in the present study was that nurses with specialized training in psychiatric/mental health nursing were more likely to have a higher level of caring. This finding is supported by Wu et al () and Brown et al (), who found that nurses who were involved in training programmes also had significantly higher scores of caring. There is more than one explanation to clarify this relationship.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…One interesting finding in the present study was that nurses with specialized training in psychiatric/mental health nursing were more likely to have a higher level of caring. This finding is supported by Wu et al () and Brown et al (), who found that nurses who were involved in training programmes also had significantly higher scores of caring. There is more than one explanation to clarify this relationship.…”
Section: Discussionsupporting
confidence: 58%
“…There is more than one explanation to clarify this relationship. First, mental health nurses who participate in specialized psychiatric mental health nursing training might feel they have a strong connection with patients and their families (Brown et al ). Similarly, when there is someone caring for them, patients and families feel personally cared for by nursing staff (Office of the Nursing & Midwifery Services ).…”
Section: Discussionmentioning
confidence: 99%
“…Patient care facilitator performance is monitored weekly via a ''dashboard'' of quality, cost, throughput, and satisfaction measures. 3 In addition to achieving aggressive throughput and early discharge targets, Baptist placed more than 80% of clinical core outcome measures in the top 10% nationally. Baptist is currently building a new 96-bed hospital based on the 12-Bed Hospital Model.…”
Section: Innovative Care Delivery Modelsmentioning
confidence: 99%